2021
DOI: 10.1167/iovs.62.9.23
|View full text |Cite
|
Sign up to set email alerts
|

Early Postnatal Oxygen Exposure Predicts Choroidal Thinning in Neonates

Abstract: To evaluate whether choroidal thickness (CT) using arm-mounted optical coherence tomography (OCT) in infants screened for retinopathy of prematurity (ROP) correlates with oxygen exposure in neonates. METHODS.OCT images were obtained in infants screened for ROP in a single level IV neonatal intensive care unit. CT was measured at three different locations: the subfoveal center and 1.5 mm from the fovea center in each direction. Correlation and regression analyses were performed to determine the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The Spectralis Flex Module (Heidelberg Engineering GmbH, Heidelberg, Germany) was used to obtain the OCT images, using an acquisition protocol consisting of seven horizontal B-scans spaced 60 to 120 microns apart through the central macula, with the foveal center defined as the shallowest point. 19 …”
Section: Methodsmentioning
confidence: 99%
“…The Spectralis Flex Module (Heidelberg Engineering GmbH, Heidelberg, Germany) was used to obtain the OCT images, using an acquisition protocol consisting of seven horizontal B-scans spaced 60 to 120 microns apart through the central macula, with the foveal center defined as the shallowest point. 19 …”
Section: Methodsmentioning
confidence: 99%
“…In consensus with previous studies [ 23 ], we also demonstrated the choroid was thinner in ROP neonates with the plus disease compared to not-plus disease. It has been suggested that the thinning of the choroid in ROP neonates may be due to oxidative stress and choroidal vascular loss [ 7 , 12 , 24 , 25 ]. This choroidal vascular loss has been proven angiographically.…”
Section: Discussionmentioning
confidence: 99%
“…They included gestational age, birth weight, PMA at imaging and the fraction of inspired oxygen (FiO 2 ) at 30 weeks, 36 weeks and the day of OCT imaging in their analysis, where higher FiO 2 at 30 weeks was independently associated with choroidal thinning implying that choroidal thickness was mainly impacted by early postnatal oxygen supplementation ( 67 ). Similar to our hypothesis, He et al also concluded that hyperoxia-induced vascular attenuation may be responsible for the choroidal thinning ( 66 , 67 ).…”
Section: Choroidmentioning
confidence: 99%
“…Several studies have found a correlation between ROP and choroidal thinning ( 8 , 15 , 16 , 67 ). In Moreno et al, we reported thinner choroid in eyes of preterm infants and in those infants with ROP ( 8 ).…”
Section: Choroidmentioning
confidence: 99%
See 1 more Smart Citation